PCR based detection of toxoplasmosis in tissue samples: A step towards detection of toxoplasmosis in meat and post mortem samples - SUDAN, VIKRANT; TEWARI, A K; SINGH, HARKIRAT (The Indian Journal of Animal Sciences, 2016)
The aim of the study was to find out a suitable marker gene for diagnosis of toxoplasmosis in tissue and meat samples during meat inspection and/or during post mortem studies. PCR was used to diagnose toxoplasmosis in ten inbred Swiss albino mice after experimental inoculation of 100 tachyzoites of laboratory maintained human RH strain of the parasite. Blood, peritoneal lavage and tissue from lung, liver spleen, brain, heart and kidney were taken from experimental murine models in duplicate. The samples were subjected to PCR, using primers directed to the multicopy of Surface Antigen 3 (SAG 3 gene). Blood, kidney and heart tissue were found negative while peritoneal lavage along with lung, liver spleen and brain tissue yielded desired positive amplicons. The significance of the studied molecule vis-Ã -vis future projections in regard to diagnosis of toxoplasmosis during meat sample examination and/or during routine post mortem is being described.